2012
DOI: 10.1021/bc300133r
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide-Containing Brushed Polyethylenimine Derivative Synthesized by Click Chemistry for Nonviral Gene Delivery

Abstract: Polyaspartamide-based disulfide-containing brushed polyethylenimine derivatives P(Asp-Az)X-SS-PEIs were synthesized via click chemistry and evaluated as nonviral gene delivery carrier. First, azide-functional poly(aspartic acid) derivatives with various azide-group densities and monoalkyne-terminated PEI with disulfide linkages were synthesized. Then, click reaction between the azide-functional poly(aspartic acid) derivative as main chain and the monoalkyne-terminated PEI as branched chain resulted in high-mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…1 H NMR spectra of P(Asp‐Az) X ‐HPA polymers (Fig. ) were determined with different solvents according to our previous work . It can be seen from Figure (A–C) that no peak around 5.3 ppm is observed, which indicates no unreacted succinimide rings existed in all obtained P(Asp‐Az) X ‐HPAs.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…1 H NMR spectra of P(Asp‐Az) X ‐HPA polymers (Fig. ) were determined with different solvents according to our previous work . It can be seen from Figure (A–C) that no peak around 5.3 ppm is observed, which indicates no unreacted succinimide rings existed in all obtained P(Asp‐Az) X ‐HPAs.…”
Section: Resultsmentioning
confidence: 98%
“…Although the PEGylation phe‐ g ‐PHPAs were synthesized as drug delivery for paclitaxel (PTX), grafting efficiency of aromatic rings to poly‐(5‐hydroxypentyl‐ N ‐α/β asparagines) (PHPA) was <50% . Because of the high selectivity and high fidelity, “click” chemistry has rapidly become a very popular method for polymer synthesis and modification . In this study, two examples of thermoresponsive polyaspartamide derivatives containing pendant aromatic structures and thermo/pH‐responsive polyaspartamide derivatives containing pendant imidazole rings were designed and synthesized successfully with very high reaction efficiency by click chemistry as depicted in Scheme .…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that a higher degree of thiolation resulted in smaller nanoparticles (Figure ) . Another important approach for thiolating PEI involves employing various kinds of crosslinkers containing disulfide linkages; this is the most common strategy for providing bioreducibility to polymers …”
Section: Introductionmentioning
confidence: 99%
“…In addition to aminobutanol and disulfide linkage, other hit functionalities used for the design of potent polymeric gene delivery vectors largely encompass oligoamine, low-molecular weight BPEI and imidazole group [12]. For example, bioreducible BPEIs obtained by disulfide-crosslinking of low-molecular weight BPEI were found to be highly potent for in vitro gene delivery followed by low cytotoxicity [13,14]. Bioreducible poly(amido amine)s with imidazole side chain displayed superior transfection activity to 25 kDa BPEI [15,16].…”
Section: Introductionmentioning
confidence: 99%